2009
DOI: 10.2308/jis.2009.23.1.97
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors Influencing the Use of Computer-Related Audit Procedures

Abstract: We provide data on the extent to which computer-related audit procedures are used and whether two factors, control risk assessment and audit firm size, influence computer-related audit procedures use. We used a field-based questionnaire to collect data from 181 auditors representing Big 4, national, regional, and local firms. Results indicate that computer-related audit procedures are generally used when obtaining an understanding of the client system and business processes and testing computer controls. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 38 publications
5
67
0
3
Order By: Relevance
“…However, using unified theory of acceptance and use of technology (UTAUT), Venkatesh et al (2003) and Bierstaker et al (2014) found a positive effect of facilitating conditions on usage behaviours regarding to personal computing and CAATTs, which was moderated by gender, age, experience, and voluntariness. Further, Janvrin et al (2009) In contrast to Davis et al (1989), Malhotra and Galletta (1999) have found that all three processes of social influence had direct effects on the user's attitude and indirect effects on their behavioural intention via attitude. It was found that identification and internalization had a strong positive effect on attitude, while compliance 1 2 3 has a weaker negative effect on attitude toward using technology.…”
Section: Background and Research Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using unified theory of acceptance and use of technology (UTAUT), Venkatesh et al (2003) and Bierstaker et al (2014) found a positive effect of facilitating conditions on usage behaviours regarding to personal computing and CAATTs, which was moderated by gender, age, experience, and voluntariness. Further, Janvrin et al (2009) In contrast to Davis et al (1989), Malhotra and Galletta (1999) have found that all three processes of social influence had direct effects on the user's attitude and indirect effects on their behavioural intention via attitude. It was found that identification and internalization had a strong positive effect on attitude, while compliance 1 2 3 has a weaker negative effect on attitude toward using technology.…”
Section: Background and Research Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, the auditing standards issued by the American Institute of Certified Public Accountants (AICPA) and Auditing Practices Board (APB) encourage the utilization of CAATTs. Janvrin et al (2009), Ahmi and Kent (2013), and Bierstaker et al (2014) identified a number of different functions of CAATTs according to these auditing standards. These functions are: evaluate fraud risk, identify journal entries and other adjustments to be tested, evaluate inventory existence and completeness (AICPA, 2002;APB, 2004aAPB, , 2004bAPB, , 2004c, select sample transactions from key electronic files, sort transactions with specific characteristics, test an entire population instead of a sample, obtain evidence about control effectiveness (APB, 2004a(APB, , 2004e, 2006PCAOB, 2010), check the accuracy of electronic files, and reperform procedures such as aging of accounts receivables (AICPA, 2001;APB, 2004aAPB, , 2004dAPB, , 2006.…”
Section: Background and Research Hypotheses Developmentmentioning
confidence: 99%
“…Recent research, however, indicates that only a minority of firms use CAATs for substantive testing because of the high level of complexity (Janvrin et al, 2009). Continuous auditing can provide much of the substantive testing in a routine manner and allow auditors to concentrate on the forensic analysis of data.…”
Section: Forensic Continuous Auditingmentioning
confidence: 99%
“…Among the factors are client, job relevance, auditing, cost and resources, technological and IT availability, personal experience, personal knowledge and support from management. Janvrin et al (2009a) examined the degree of using computer-related audit procedures and whether the use of computer-related audit procedures are influenced by control risk assessment and audit firm size. Another study by Janvrin et al (2009b) discovered that performance expectancy and organizational and technical infrastructure support affects the possibility that auditors might employ CAATTs.…”
Section: It Implementationmentioning
confidence: 99%
“…For instance, Ahmi & Kent (2013), Debreceny et al (2005) and Wehner & Jessup (2005) emphasis on generalised audit software (GAS) while Rosli et al (2012), Janvrin et al (2009a), Janvrin et al (2009b) and Mahzan & Lymer (2008) examine on Computer Assisted Auditing Tools and Techniques (CAATTs). Most of the above studies were focus on the either internal auditors or external auditors or covering both internal auditors and external auditors in private sector.…”
Section: Introductionmentioning
confidence: 99%